Peningkatan Konsentrasi Belajar Anak Attention Deficit Hyperactive Disorder dengan Menerapkan Strategi Pembelajaran Station Rotation - Nur Aufa Makmur; Marlina Marlina (Jurnal Penelitian Pendidikan Khusus, 2023)
Children with Attention Deficit Hyperactivity Disorder (ADHD) typically struggle with concentration, which includes the ability to concentrate on learning. The researcher discovered a child with ADHD of the inattentive type in an inclusive school with a low concentration based on the assessment results. Subject were chosen based on the results of the identification and assessment performed by the researchers using the identification tool for children with special needs and the duration instrument. The station rotation (SR) learning strategy is a differentiated learning strategy that uses stations to achieve learning objectives over a set time, with children grouped according to readiness, interest, and learning profile. This study aimed to see how effective SR learning strategies were at increasing learning concentration in children with ADHD. The experimental method was used in this study, with a single subject research (SSR) reversal design model type A-B-A. Data were analyzed using visual chart analysis, which included in-condition and between-condition analysis. The results showed that children with ADHD in the inclusion class improved their ability to concentrate on learning. Children with ADHD in inclusive schools will be studied using SR learning strategies to increase effective learning concentration.